(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
This research examines the transformation of Prawirotaman Street, Yogyakarta, into a tourism-oriented mixed-use corridor and assesses publicness as an operative indicator of a sustainable built environment. Publicness is evaluated through three principal variables: social (interaction, inclusivity, participation), economic (commercial dominance, ownership patterns, livelihood transitions), and environmental (accessibility, vegetation, drainage, spatial comfort), across spatial units comprising a 500 m corridor, 481 m pedestrian pathways, building interfaces, and 21 designated observation points. A qualitative socio-spatial methodology was employed, integrating the theory of publicness (Carmona, 2015) with the production of space framework (Lefebvre, 1991). Data collection involved 19 structured field observations (spanning morning–evening cycles), in-depth interviews, and field surveys, reinforced by a synthesis of recent scholarly literature. The analytical process utilized thematic and comparative socio-spatial techniques. The findings indicate that 65% of buildings have transitioned to tourism-related functions, while only 26% of pedestrian space remains effectively functional, reflecting diminished accessibility and escalating privatization. Although economic activities have intensified, this growth is not accompanied by proportional improvements in social inclusivity or environmental quality. Publicness endures primarily at a micro-spatial scale through temporary, consumption-driven interactions. This study conceptualizes publicness as a comprehensive sustainability metric and underscores the necessity for pedestrian-oriented design strategies, ecological enhancements, and collaborative governance frameworks to re-establish socio-spatial equilibrium within tourism corridors.